Apical surgery as cystic lesion treatment for Barodontalgia prevention: a case report - Marilia Fagury Videira Marceliano-Alves; Carlos Vieira Andrade-Junior; Flávio Rodrigues Ferreira-Alves; Alejandro Ron Perez; Sankalp Verma (Universidad de Antioquia, 2018)
Barodontalgia is not a pathology but a symptom of a subclinical oral problem that, although rare, may affect patients subjected to atmospheric pressure changes and have an influence on flights. This paper aims to discuss the clinical characteristics of pathologies related to the etiology of barodontalgia, as well as differential diagnoses, treatments, and prevention. This paper reports a case of a Brazilian air force officer who went to the Santos Dumont Air Force Dental Clinic reporting pain in the anterior maxillary during a flight. An endodontic treatment followed by periradicular surgery was performed, in order to quickly seal the bone lesion and to avoid new cases of barodontalgia. This work demonstrated a successful approach of a periradicular lesion solved by surgical treatment in order to avoid new cases of barodontalgia during flights. In addition, this paper highlights the importance of deepening knowledge on this event and the need for periodic oral and dental assessment, as well as conclusive treatment in aircrew members in order to prevent aircraft accidents.